Role of superdisintegrants in enhancing dissolution rate of valsartan - Narjess Baabaa; Nisrin Kaddar; Nathalie Moussa (مجلة جامعة تشرين للدراسات والبحوث العلمية، سلسلة العلوم الصحية, 2024)
Drug solubility and dissolution rate vitally affects its oral bioavailability. Unfortunately, most marketed drugs exhibit low solubility. Valsartan, an angiotensin II receptor blocker, and one of the most effective and commonly used anti-hypertension agents, suffers from low solubility and dissolution rate, and therefore low oral bioavailability. As such, enhancing its dissolution rate could prove very beneficial for the management of hypertension. This study made use of the superdisintegrants crospovidone and croscarmellose, which exhibit ameliorating properties such as wicking and swelling, in order to enhance the disintegration profile of valsartan capsule formulations, and in turn improve its dissolution rate. Seven formulations were prepared and subjected to various quality assessment tests, concluding with an in-vitro dissolution test to identify the optimal formulations.